2023
DOI: 10.3390/metabo13020272
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Analytical Methods for Quantitative Determination of Coenzyme Q10 in Foods

Abstract: Food analysts have developed three primary techniques for coenzyme Q10 (CoQ10) production: isolation from animal or plant matrices, chemical synthesis, and microbial fermentation; this literature review is focused on the first method. Choosing the appropriate analytical method for determining CoQ10 in a particular food product is essential, as this analyte is a quality index for healthy foods; various associations of extraction and quantification techniques are available in the literature, each having advantag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…HPLC with DA detection at 275 nm is the most common technique to estimate CoQ10 in foods, generally using calibration with an external standard [ 9 ]. For example, in 2000, it was used by Mattila et al [ 13 ] to measure CoQ10 levels in pork heart, beef meat, and Baltic herring flesh by applying direct extraction with n -hexane/ethanol (5:1, v / v ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…HPLC with DA detection at 275 nm is the most common technique to estimate CoQ10 in foods, generally using calibration with an external standard [ 9 ]. For example, in 2000, it was used by Mattila et al [ 13 ] to measure CoQ10 levels in pork heart, beef meat, and Baltic herring flesh by applying direct extraction with n -hexane/ethanol (5:1, v / v ).…”
Section: Resultsmentioning
confidence: 99%
“…The lowest concentration of CoQ10 was found in WPC (36.56 µg CoQ10/g sample), while in HPC, it was not detected. Most studies have only focused on determining CoQ10 in raw materials and oils [ 9 , 34 ], and, to our knowledge, this is the first one conducted on oil press cakes. In the study of Rodríguez-Acuña et al [ 34 ], CoQ10 was isolated by solid-phase extraction (SPE) from crude oil of rapeseed and refined oil of sunflower, showing levels of 46.4 and 8.7 µg/g, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most CoQ10 supplements are expensive and difficult to promote in the daily lives of the entire population. The exogenous acquisition methods of CoQ10 include various natural foods in addition to nutritional supplements [11,12]. Previous studies have also found a significant non-linear correlation between the total intake of CoQ10 from dietary sources and risk factors related to cardiovascular disease, such as C-reactive protein [13].…”
Section: Introductionmentioning
confidence: 99%